FAKTOR-FAKTOR YANG MEMENGARUHI M ANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - Marvellyn, Marvellyn; Susanto, Liana (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to obtain empirical evidence about factors affecting earnings management in manufacturing companies listed on Indonesia Stock Exchange for the years 2017-2020. Sample selection technique that used is purposive sampling method and acquired 51 companies. Data processing technique using multiple linear regression analysis and assisted by Eviews 12 software. The results showed that leverage has positive significant effect on earnings management, while firm size, institutional ownership, and independent board commissioners do not have significant effect on earnings management. The implication of this research is to provide information for investors that should read up the company's financial statements carefully before decided to invest in a company.